Beneficiamento e caracterização de resíduos gerados na produção de blocos cerâmicos visando à aplicação como adição pozolânica - Igor Soares Pinheiro (2008)
The use of red ceramics bricks finely grinded as pozzolanic addition to cements, mortar and concrete reveals a viable alternative, with technical, economic and environmental advantages, joining wasted material by the industry, which not always has a proper destination, to the input and products wide used in the civil construction. This work presents the improvement and characterization of these residues, objectifying its application as pozzolanic addition to mortars, cements and concretes. Therefore, two different samples had been used: structural and seal ceramic bricks. The samples were grinded during 150 minutes, getting values below of 19% in the sieve #325 (45 m). The density gotten through of pycnometer was of 2,82 and 2,81 and g/cm ³, respectively. The surface area of the samples was 4,26 and 8,46 m²/g, respectively, being superior to the average values gotten in the Portland cement. The X-rays diffraction analysis presented crystalline peaks identified as quartz and hematites, and partially identified, as rutilo and microcline, corroborating with the elements gotten in the X-rays fluorescence spectrometry. The scanning electron microscopy and microanalysis had shown samples with irregular morphology, with predominance of the oxides SiO2, Al2O3 and Fe2O3, whose addition was superior 92%. The pozzolanic activity tests with Portland cement were satisfactory if compared to NBR 5752 values, getting superior indexes of pozzolanic activity to 78%, with required water below 101%. The pozzolanic activity tests with pozzolanic Portand cement classified the samples as being pozzolanic materials. The obtained results revealed to be promising for the use of the studied wastes, presenting physiochemical indexes and pozzolanic activity within range allowed by the Brazilian norms.